A Structurally Characterized Cobalt(I) σ‐Alkane Complex. Issue 15 (20th February 2020) - Boyd, Timothy M.; Tegner, Bengt E.; Tizzard, Graham J.; Martínez‐Martínez, Antonio J.; Neale, Samuel E.; Hayward, Michael A.; Coles, Simon J.; Macgregor, Stuart A.; Weller, Andrew S.
Abstract: A cobalt σ‐alkane complex, [Co(Cy2 P(CH2 )4 PCy2 )(norbornane)][BAr F 4 ], was synthesized by a single‐crystal to single‐crystal solid/gas hydrogenation from a norbornadiene precursor, and its structure was determined by X‐ray crystallography. Magnetic data show this complex to be a triplet. Periodic DFT and electronic structure analyses revealed weak C−H→Co σ‐interactions, augmented by dispersive stabilization between the alkane ligand and the anion microenvironment. The calculations are most consistent with a η 1 :η 1 ‐alkane binding mode. Abstract : A cobalt σ‐alkane complex was synthesized by a single‐crystal to single‐crystal solid/gas hydrogenation from a norbornadiene precursor, and its structure was determined by X‐ray crystallography. Periodic DFT and electronic structure analyses revealed weak C−H→Co σ‐interactions, augmented by dispersive stabilization between the alkane ligand and the anion microenvironment.